2010
DOI: 10.1007/s00464-009-0853-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection with intracorporeal anastomosis for colon carcinoma located in the splenic flexure

Abstract: Laparoscopic partial resection seems to be feasible and safe for the treatment of early-stage and locally advanced SF cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…A mini-invasive approach proved to be especially suitable for splenic flexure mobilizing; due to its fixed position, some Authors suggested the use of Da Vinci system for this subgroup of colic cancer. Effectively, laparoscopic robot-assisted resection seems to be a promising approach for splenic flexure cancer treatment, since it allows finer manipulation which can decrease the risk of spleen injury [ 15 ]. Anastomosis is generally side-to-side performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mini-invasive approach proved to be especially suitable for splenic flexure mobilizing; due to its fixed position, some Authors suggested the use of Da Vinci system for this subgroup of colic cancer. Effectively, laparoscopic robot-assisted resection seems to be a promising approach for splenic flexure cancer treatment, since it allows finer manipulation which can decrease the risk of spleen injury [ 15 ]. Anastomosis is generally side-to-side performed.…”
Section: Discussionmentioning
confidence: 99%
“…A fast track protocol was performed in these patients, with good outcome in term of short terms complications and with shorter hospital stay. Preservation of inferior mesenteric and middle colic arteries could account for the good anastomotic healing, much more than improved experience with this technique [ 15 ]. Attemping to answer to all these controversies, we believe that when laparoscopic splenic flexure resection is performed after an adequate learning curve regarding other colon cancer locations, and if it is performed on appropriate patient groups with accurate preoperative diagnosis, this procedure should be considered a safe and useful treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has studied earlier by Griffith et al, demonstrated anatomical description of colon blood supply in 100 cadavers, revealed that splenic flexure colon supplied by LCA in 89% of cases and 11% by MCA. 12 As lympahtic spread will follow arterial system in their drainage. 13 Therefore, SFC carcinoma has dual lymphatic drainage: to the superior mesenteric vessel and to the inferior mesenteric vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have specifically investigated the use of laparoscopic left hemicolectomy for cancer (11). However, surgical approaches for transverse or descending colon cancer vary considerably depending on the relative location of the tumor.…”
Section: Discussionmentioning
confidence: 99%